1995
DOI: 10.1152/jn.1995.73.6.2279
|View full text |Cite
|
Sign up to set email alerts
|

Properties of superior vestibular nucleus flocculus target neurons in the squirrel monkey. II. Signal components revealed by reversible flocculus inactivation

Abstract: 1. Seven upward eye velocity flocculus target neurons (FTNs) and two flocculus projecting neurons (FPNs) were studied before and after ipsilateral flocculus inactivation by injection of muscimol in the alert squirrel monkey. An additional seven FTNs and seven FPNs recorded from the corresponding FTN and FPN areas were recorded after injection. Response properties of FTNs and FPNs were characterized by visual-vestibular interaction paradigms and were compared before and after flocculus inactivation. 2. In FTNs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The cerebellum has long been implicated in eye movement adaptation and internal models (Shidara et al, 1993;Wolpert et al, 1995;Glasauer, 2003). EH neurons are the recipients of direct inhibition from Purkinje cells in the cerebellar flocculus and ventral paraflocculus and are shown to participate in motor learning (Lisberger et al, 1994;Zhang et al, 1995). Therefore, the present findings and those of Angelaki and Dickman (2003), showing that EH responses might be consistent with coding the half-angle rule during pursuit, provide strong support that the cerebellum might be constructing a forward model for slow eye movements.…”
Section: Forward Model and Eh Cellssupporting
confidence: 70%
“…The cerebellum has long been implicated in eye movement adaptation and internal models (Shidara et al, 1993;Wolpert et al, 1995;Glasauer, 2003). EH neurons are the recipients of direct inhibition from Purkinje cells in the cerebellar flocculus and ventral paraflocculus and are shown to participate in motor learning (Lisberger et al, 1994;Zhang et al, 1995). Therefore, the present findings and those of Angelaki and Dickman (2003), showing that EH responses might be consistent with coding the half-angle rule during pursuit, provide strong support that the cerebellum might be constructing a forward model for slow eye movements.…”
Section: Forward Model and Eh Cellssupporting
confidence: 70%
“…Even though FTN response behavior during saccades and VOR suppression could vary greatly, their unique characteristics include a strong eye-velocity sensitivity with a small and often non-linear eye-position sensitivity. FPNs, on the other hand, have been described as cells with small eye-movement sensitivity and represent distinctly different and nonoverlapping populations from FTNs (Nagao et al 1997;Zhang et al 1993Zhang et al , 1995a. Neuroanatomical and electrophysiological studies have identified FTNs in the rostral medial and ventrolateral vestibular nuclei (Langer et al 1985a;Lisberger et al 1994;Nagao et al 1997;Sato et al 1988).…”
Section: Classes Of Vestibuloocular Neurons and Comparison Of Their Rmentioning
confidence: 99%
“…Among the four major vestibular nuclei, the SVN receives inputs predominantly from the semicircular canals and sends axons to the oculomotor nucleus, the cerebellar nodulus, uvula and flocculus, and the ventral posterior nuclear complex of the thalamus, which in turn projects to the cortical areas relevant to vestibular sensations [12]. Consequently, slightly different from the other vestibular nuclei which are also essential for posture adjustments of the head and/or body, the SVN primarily participates in vertical vestibulo-ocular reflexes and holds a key position in gaze control [12,14,15,16], together with the MVN. Therefore, the present results that histamine directly excites the SVN neurons suggest that the histaminergic innervation from the hypothalamus on vestibular nuclei may actively participate in stabilizing not only head and posture through the MVN and LVN, but also gaze through the MVN as well as the SVN.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four nuclei in the central vestibular nuclear complex, the SVN, together with the MVN, receives fibers predominantly from the semicircular canals and sends fibers through the medial longitudinal fasciculus rostrally to oculomotor centers and caudally to the spinal cord [12,13]. Both of these two nuclei actually hold a key position in vestibulo-ocular reflexes and gaze control [12,14,15,16], and are closely related to nystagmus [17,18]. …”
Section: Introductionmentioning
confidence: 99%